Vitamin D and Tinospora cordifolia modulate TLR3 and TLR4 pathways, reduce inflammation, and maintain antimicrobial peptide levels in infected mice - Jamil Ahmad Shobrun; Widyarti Sri; Setiawan Meddy; Rifa’i Muhaimin (BIO Web of Conferences)
The activation of Toll-Like Receptor-3 (TLR3) and Toll-Like Receptor-4 (TLR4) signalling pathways is a regular pathway for immune system activation during infection. This study aimed to investigate the effects of vitamin D (VD) and Tinospora cordifolia ethanol extract (TC) on TLR3 and TLR4 receptor protein expression, proinflammatory cytokine (IL1 and IL-6) production, and antimicrobial peptide cathelicidin (CAP) production in CD11b+ cells of mice infected with Escherichia coli. The treatments consisted of administration of VD (0.325 µg/kg bw), TC (100 mg/kg bw), and a combination of both in the same dose for 28 days, followed by induction of E. coli infection on day 29. The flow cytometry method was analyzed of TLR3, TLR4, IL-1, IL-6, and CAP expression in CD11b+ cells of experimental animals. The following measurement results were compared with healthy controls and infected animals with the significance of differences between treatments analyzed by One-way ANOVA with p < 0.05. The results showed that administering VD, TC, and a combination of both reduced the expression of TLR3, TLR4, and IL-1 compared to treating infected animals. The combination treatment of VD + TC increased CAP production more than all other treatments. This significant finding suggests that the combination of VD + TC has the potential to control inflammation without disrupting the body’s defence mechanisms against infection, providing valuable insights for the field of immunology.